Behavior of Toddler Mothers Against Disorders Due to Iodine Deficiency - Sulistyo Andarmoyo; Lumastari Ajeng Wijayanti; Ony Wibriyono Angkejaya; Hasnia Ahmad; Nelly Mariati (Jurnal Penelitian Pendidikan IPA, 2023)
One of the four nutritional problems in Indonesia is Iodine Deficiency. Iodine deficiency is a set of symptoms that occur due to continuous lack of element Iodine and long period of time. Iodine is needed by everyone, especially during the growth period. Iodine deficiency will cause impaired physical growth and low intelligence the quality of human resources is getting worse. This study aims to analyze the behavior of mothers under five towards Iodine Deficiency Disorders. This Research There are three data collection methods that are often used in qualitative research, namely: 1) participatory observation 2) in-depth interviews and 3) focus group discussions. That The population is a survey of 30 housewives who were interviewed, 25 of whom did not understand GAKI and did not understand the benefits of iodized salt. They taken by propositional stratified random sampling. Data collection is done in the form interview, observation and salt test. Based on the research results, it can be concluded that of the 30 housewives who were respondents, 30 of them had insufficient knowledge of IDD.